Framework for methodical review of literature on leadership competencies - Sateesh V. Shet; S.V. Patil; Meena R. Chandawarkar (Cogent Business & Management, 2017)
The purpose of this paper is to examine and discuss scholarly literature on leadership competencies (LCs) through a multi-dimensional framework. This research adopts qualitative research method using scholarly literature. An attempt is made to combine the outcomes of these literatures into a more integrative framework of competency studies, offering a suggestion for further research. The findings reveal that the literature on LCs can be categorised using structured framework for better understanding. The literature has been categorised in different perspectives—Leadership levels, Function specific, Job specific, Geography specific, Generic Competency Specific. This framework provides the basis for future research to test the efficacy of framework. The framework provided in this paper incorporates main findings of previous research and as such it may serve as a starting point of practitioners in planning of different extended research in each of the dimensions identified.
Keywords: 650